x(x+1)分之1+(x+1)(x+2)分之1+(x+2)(x+3)分之1 以此类推,最后一个是(x+8)(x+9)分之
2个回答
=1/x-1/(x+1)+1/(x+1)-1/(x+2)+……+1/(x+8)-1/(x+9)
=1/x-1/(x+9)
=9/(x²+9x)
相关问题
X(X+z)分之1+(X+1)(X+2)分之1+.+(x+8)(x+9)分之1=x9(x+9)分之2x+3
(1+x+3分之x-3)÷x方-9分之2x 化简x-2分之x方×x方+2x分之2+x-x-2分之1 x分之1-x-1分之
①x²-1分之3x-1+1-x分之x=2 ②x²-4分之2x+2-x分之1=3分之1
(1) x-2分之4x-1=2-x分之3 (2) x-3分之x-2x-6分之1=2分之1 (3) x+3分之x=1+x-
1-x的平方分之2=1+x分之3 x-1分之1=x+1分之x+2-1 x-1分之2x+x+2分之2=2
解下列方程①-3分之1+2分之X=2X②2分之1-X-3分之X-8=1③2分之X+1-2分之2X-1=2
x-2分之4x-(1)=2-x分之3 x-3分之x-2x-6分之1=2分之1 x+3分之x=1+x-1分之2 解分式方程
(1-x)分之1+(1+x)分之1+(1+x^2)分之2+(1+X^4)分之4+(1+x^8)分之8+(1+x^16)分
2分之1-x<3分之x+9-5 3分之2x+1+6分之x+1>6分之2-x 0.5分之x-1+0.75分之2x-1
1 3X-1=2分之X2 5分之3X-2-2分之X-2=3分之8-2X3 X-3分之1+X=24 0.3分之X-1-0.